Upaya Peningkatan Motivasi dan Prestasi Belajar Pendidikan Agama Islam Materi Menghindari Perilaku Tercela Melalui Metode Team Quiz Pada Siswa Kelas VIII-F SMP Negeri 2 Pare Kabupaten Kediri - Ida Mahmudah (Jurnal Simki Postgraduate, 2023)
This classroom action research aims to increase motivation and learning achievement in Islamic Religious Education for class VIII-F students of SMP Negeri 2 Pare, Kediri Regency. This research is devoted to the material Avoiding Disgraceful Behavior. The research subjects were 33 students of class VIII-F of SMP Negeri 2 Pare, Kediri Regency. This study used the team quiz method, which is a learning method with a study group division system where learning material is divided according to the study group so that the study group will have the opportunity to be a group of questioners and answerers. This type of Classroom Action Research is carried out in cycles using the Kemmis and Taggart models with details of: (i) planning (ii) implementing actions (iii) observation (iv) reflection. The types of data obtained are qualitative data and quantitative data. Qualitative data is data obtained in teaching and learning activities in the form of observation. Meanwhile, quantitative data is data on learning outcomes obtained by testing. The result is that the team quiz method can increase motivation to study Islamic Religious Education material Avoiding Disgraceful Behavior in Class VIII-F students of SMP Negeri 2 Pare, Kediri Regency. This is evidenced by the increased student learning activity from pre-cycle 45% to 60% in cycle 1, then increased 90% in cycle 2. The team quiz method can improve learning achievement in Islamic Religious Education material Avoiding Disgraceful Behavior in Class VIII-F students of SMP Negeri 2 Pare, Kediri Regency. This is evident from the average learning outcomes reaching 85.15 in cycle 2 with a classical completeness percentage of 93.93% from the previous results, namely cycle 1, the average learning outcome was 75.75 with a classical completeness percentage of 69.69%.